Clinical analysis of patients with deep sternal wound infection-induced sepsis: a retrospective cohort study - Bin Song; Zhentian Cui; Hongyan Ju; Yue Sun; Dandan Liu; Guanggang Li (Emergency and Critical Care Medicine)
Abstract. Background. This study aimed to summarize the clinical characteristics of patients with deep sternal wound infection-induced sepsis after median sternotomy and improve the treatment outcomes of infection-related sepsis. Methods. A retrospective cohort study was conducted on 21 patients with deep sternal wound infection-induced sepsis after median sternotomy who were admitted to the Department of Critical Care. The clinical manifestations, laboratory test results, infection control, and organ and nutritional support of the patients were summarized, and the follow-up data were obtained. Results. The primary symptoms of deep sternal wound infection-induced sepsis included dyspnea, high fever, chills, and altered state of consciousness. Laboratory test results revealed increased inflammatory markers and decreased oxygenation index. Renal and liver function injury were observed in 8 and 4 patients, respectively; 18 and 12 patients demonstrated elevated D-dimer and N-terminal Pro B type natriuretic peptide levels, respectively. Of the 8 patients whose wound secretions tested positive for bacteria, Acinetobacter baumannii and Staphylococcus aureus infections were present in 6 and 2 patients, respectively. One of the 6 patients whose blood cultures tested positive for bacteria demonstrated Candida albicans infection. Fifteen patients received ventilator-assisted ventilation and 2 patients received renal replacement therapy. Of all the 21 patients, 17 were cured, 2 died, and 2 were discharged. Conclusion. Postmedian sternotomy sepsis attributed to a deep sternal wound infection usually results from a preexisting condition. The most prominent clinical manifestation is dyspnea, which is sometimes accompanied by the impairment of organ function. Infection prevention, proper nutrition support, and maintenance of healthy organ function are the cornerstones for successful treatment outcomes.